Pengaruh Financial Literacy dan Financial Behavior Terhadap Keputusan Berinvestasi Logam Mulia (Emas) : Studi Kasus Toko Emas Sejati Samarinda - Fajrial Adzikra; Hidayani Hidayani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The increasing public interest in gold investment as a relatively stable and low-risk investment instrument motivated this study. This research aims to analyze the influence of financial literacy and financial behavior on investment decisions in precious metals (gold) among consumers of Toko Emas Sejati Samarinda. The study employed a quantitative approach using a survey method by distributing questionnaires to 150 respondents who were consumers of Toko Emas Sejati Samarinda. The data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares with the assistance of SmartPLS 4 software. The results indicate that financial literacy and financial behavior influence gold investment decisions. These findings suggest that individuals with better financial literacy and more responsible financial behavior tend to make more rational and well-directed decisions when investing in gold